Beyond Sorry Beyond Sorry - Vadiveloo, David (Australia, 2003)
Poor quality sound. Film is a donation of the Margaret Mead Festival, supported by OSI-Budapest. Duration: 00:53:00 As a young girl, Aggie Abbott hid and watched as her cousin Zita Wallace was stolen from their traditional Aboriginal community while Aggie herself was not. They were both ‘half-caste’ kids. Aggie and Zita were separated for over fifty years. Zita Wallace, now 64, has decided to reconstruct her identity, her life and her history. With Aggie as her guide, Zita is learning everything she needs to know about being a traditional Aboriginal woman. David Vadiveloo’s moving documentary reveals the complex pressures that come to bear when an urban Aboriginal woman tries to return to the family she was taken from as a child. It is an intimate story of cultural conflict, remarkable courage and generosity, of the ties that bind us to our kin, and of two women from the same land trying hard to reconcile two very different worlds.